Implementasi Fuzzy Tsukamoto pada Sistem Internet of Things Budidaya Tanaman Bayam - Andrianto Suherman; Destriana Widyaningrum (SMATIKA JURNAL : STIKI Informatika Jurnal, 2024)
Agriculture is a major sector of livelihood for Indonesians, but often faces challenges such as climate change, resource management, and poor harvesting. One is that spinach cultivation is often controlled by environmental conditions such as high heat temperatures and excessive rainfall, which can lead to a decrease in spinach quality to failure to harvest which can be detrimental to farmers and affect the sale price of spinach. The Internet of Things (IoT) technology is a solution to improve agricultural efficiency by monitoring environmental conditions such as soil humidity, temperature and water requirements in real time. The research aims to implement the fuzzy logic used to address the complexity of data obtained from IoT sensors. An automatic control system uses a servo motor based on sensors of soil humidity, air temperature, and rain. The system applies Tsukamoto's fuzzy logic method to the Arduino Uno R3 device that consists of phases of fuzzification, rule formation, inference process, and deffuzification. The monitoring of spinach cultivation using the IoT system was conducted for 7 days under controlled conditions inside the pot. The results of the study showed fuzzy motion based on the input according to the conditions of the spinach growing environment, shown on observation day 5, no rain conditions, heat temperature 330 Celsius and soil humidity 69%, moving servo 79.20 covering the area of the pot, according to defuzification values. With this result, Tsukamoto's fuzzy method can be applied to IoT systems in agriculture, in particular to control the movement of servo motors to protect spinach crops according to climate-affected environmental conditions.